The Golden Horde State in the System of International Relations » - I.М. Mirgaleev (Золотоордынское обозрение)
The present article examines the place of the Golden Horde in the system of international relations of the 13th–14th centuries as well as directions of its foreign policy. To determine the place of the ulus of Jochi in the international system the author suggests to disclose the subject through illumination of such important issues as: – the Mongol conquests and creation of the Chingisid state entities, the establishment of a new international order. – formation of the ulus of Jochi as an independent State and its role in the Chingisid States’ relations, the kurultai of 1269. – international activities of the Golden Horde State during the period of its might. – interstate coalitions in the global geopolitics and national interests of the ulus of Jochi in international systems. – The role and place of the Golden Horde in the international life of the second half of the 14th – early 15th centuries. The program activity of the Jochids in a new geopolitical situation of the late 14th – early 15th centuries. The author believes that the establishment of the Golden Horde State occurred in three phases (1207–1241, 1242–1259, 1260–1269). The Jochids’ policy towards their neighbors and other Chingisid states formed during this time. Both the Distemper of the 1360–70’s in the ulus of Jochi and destruction of all other Chingisid States resulted in the Golden Horde’s loss of its place in the system of international relations. Therefore, the program activity of the Jochids in a new geopolitical situation of the late 14th – early 15th centuries, was aimed at restoring the international authority of the State. The author considers the directions of the Golden Horde foreign policy, which were laid down during the reign of Berke khan and remained a priority until the end of the 14th century.